Ultrasound‐guided percutaneous aspiration of hyperreactio luteinalis avoids laparoscopic untwisting of ovarian torsion. (2nd July 2015) - Sakae, C.; Sato, Y.; Taga, A.; Satake, Y.; Emoto, I.; Maruyama, S.; Kim, T.
Abstract Hyperreactio luteinalis (HL) is characterized by multicystic bilateral enlargement of the ovaries and is a self‐limiting benign condition associated with pregnancy or trophoblastic disease. Since HL regresses spontaneously over time, it should be managed conservatively as long as the patient's condition permits; torsion of the enlarged ovaries is believed to be the only exception that mandates surgical intervention. Here, we describe a case of HL complicated by ovarian torsion that was treated successfully without surgical intervention. A 33‐year‐old woman was admitted to our hospital owing to acute abdomen. Nine days previously, she had had a stillbirth caused by hydrops fetalis at 24 weeks' gestation. The characteristic findings observed on magnetic resonance imaging (MRI) led to the diagnosis of HL complicated by torsion of the enlarged left ovary. Emergency laparoscopic detorsion of the ischemic left ovary was planned. Aiming to reduce the risk of cystic injury and bleeding at the trocar insertion site, volume reduction of the left ovarian cyst was performed by percutaneous aspiration. The patient's pain diminished rapidly and laparoscopic surgery was deferred. Subsequent MRI revealed that gadolinium enhancement of the left ovarian tumor had been restored, indicating spontaneous detorsion of the left ovary. The patient remained asymptomatic and was discharged from the hospital 12 days after aspiration of the cyst. From this experience, we propose that, in cases of ovarian torsion occurring in large functional cysts, including HL, volume reduction by percutaneous cyst aspiration should be considered before performing emergency laparoscopic surgery. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.